Controlled ring‐opening polymerization of trimethylene carbonate and access to PTMC‐PLA block copolymers mediated by well‐defined N‐heterocyclic carbene zinc alkoxides. (20th May 2014) - Fliedel, Christophe; Mameri, Samir; Dagorne, Samuel; Avilés, Teresa
<x xml:space="preserve">Abstract</x> Four novel Zinc–NHC alkyl/alkoxide/chloride complexes (4, 5, 9 and 9′) were readily prepared and fully characterized, including X‐ray diffraction crystallography for 5 and 9′. The reaction of N‐methyl‐N′‐butyl imidazolium chloride (3.HCl) with ZnEt2 (2 equiv.) afforded the corresponding [(CNHC)ZnCl(Et)] complex (4) via a protonolysis reaction, as deduced from NMR data. The alcoholysis of 4 with BnOH led to quantitative formation of the dinuclear Zn(II) alkoxide species [(CNHC)ZnCl(OBn)]2 (5), as confirmed by X‐ray diffraction analysis. The NMR data are in agreement with species 5 retaining its dimeric structure in solution at room temperature. The protonolysis reaction of N‐(2, 6‐diisopropylphenyl)‐N′‐ethyl methyl ether imidazolium chloride (8.HCl) with ZnEt2 (2 equiv.) yielded the [(CNHC)ZnCl(Et)] species 9. The latter was found to be reactive with CH2Cl2 in solution and to cleanly convert to the corresponding Zn(II) dichloride [(CNHC)ZnCl2]2 (9′), whose molecular structure was also elucidated using X‐ray diffractometry. Unlike Zn(II)–NHC alkoxide species 1 and 2, which contain a NHC flanked with an additional N‐functional group (i.e. thioether and ether, respectively), the Zn(II) alkoxide species 5 incorporates a monodentate NHC ligand. The Zn(II) complexes 1, 2 and 5 were tested in the ring‐opening polymerization (ROP) of trimethylene carbonate (TMC). All three species are effective initiators for the controlled ROP of trimethylene carbonate, resulting in the production of narrow disperse PTMC material. Initiator 1 (incorporating a thioether moiety) was found to perform best in the ROP of TMC. Notably, the latter also readily undergoes the sequential ROP of TMC and rac‐LA in the presence of a chain‐transfer agent, leading to well‐defined and high‐molecular‐weight PTMC/PLA block copolymers. Copyright © 2014 John Wiley & Sons, Ltd.